Effectiveness of Mental Health Training Module Gap Action Programme (mhGAP) in Increasing Knowledge and Skills of Primary Care Physicians in Diagnosing Depression Disorders in the Gunungkidul District - Novi Fitri Yani; Carla R Marchira; Wahyudi Istiono (Faculty of Medicine, Public Health, and Nursing, 2018)
Background: Depression occurs in 3-8% of the population of the world and ranks fourth in the world's most prevalent diseases. Based on data from Riskesdas 2013, the rate of mental disorders (depression and anxiety) reached 6% for ages 15 and older. The mental disorder most prevalent in primary care is the depressive disorder (10%), but the diagnosis of depression by general practitioners in primary care is only 1%. Coverage of mental health in primary care is low, partly because primary care physicians who are in Community and Primary Health Care Centers (Puskesmas) are still experiencing difficulties in diagnosing mental disorders, especially depression.Objective: To determine the effectiveness of mhGAP training in improving the knowledge and skills of primary care physicians in diagnosing and treating depression in Gunungkidul.Research Methods: This study was a quasi-experimental research with pretest-posttest design with one group, in order to find a causal relationship involving one treatment group.Results: The knowledge of the primary care physician improved about diagnosis of depression before and after intervention training modules, p=0.000. Patients with depression mostly suffered in the female group ages 19-60 years old. An increase in the diagnosis of depression after training mhGAP with validation by a psychiatric specialist was at 49.41%.Conclusion: Training with modules mhGAP improved education for physicians in the diagnosis of depression and improved referral rates of depression cases from community health centers to district hospitals in Wonosari.